F29. EXPLORATORY ANALYSIS OF THE RELATIONSHIP BETWEEN THE CHANGE FROM BASELINE IN PANSS AND BNSS RATING SCALES. (9th April 2019) - Kott, Alan; Xingmei, Wang; Daniel, David
Abstract: Background: Schizophrenia with predominant negative symptoms represents a significant unmet medical need. New instruments measuring the severity of negative symptoms are being implemented into clinical trials to improve the ability to accurately measure these symptoms. We have previously reported on the relationship between the Positive and Negative Syndrome Scale and the Brief Negative Symptom scales. In the current analysis we intend to assess the relationship between the change from baseline between these two scales. Methods: Data from 829 schizophrenia clinical trials subjects with both PANSS and BNSS data available were used. Controlling for baseline severity using the baseline CGI severity score we conducted exploratory regression analyses assessing the relationship between the change from baseline in the BNSS scale and change from baseline in PANSS negative subscale and PANSS negative factor(NFS). Additionally, we explored the relationship in change in the avolition/apathy factor as well as the expressive deficits factor between the BNSS and the PANSS. Given the exploratory nature of the analyses we did not correct for multiplicity. Results: Strong correlations were identified in change from baseline between BNSS scale and the PANSS NFS and the PANSS negative subscale (r = 0.81 and r = 0.78, respectively). Considerably weaker, but still significant correlations were seen in change from baseline in the apathy/avolition factor and the expressive deficits factor between the BNSS and the PANSS (r = 0.59 and r = 0.62, respectively). The following equations were derived: BNSSΔ = 3.84 + 1.73*NFSΔ -0.94*CGI-S[Baseline] BNSSΔ = 5.46 + 1.75*PANSS-negativeΔ – 1.31*CGI-S[Baseline] BNSS[apathy/avolition]Δ = -0.57 + 1.50*PANSS[apathy/avolition]Δ +0.05* CGI-S[Baseline] BNSS[expressive_def]Δ = -0.38 + 0.82*PANSS[expressive_def]Δ +0.04* CGI-S[Baseline] Discussion: Our data indicate strong relationship between the change in BNSS total score and change in PANSS negative subscale / negative factor from baseline. In addition, our data indicate a considerably weaker relationship between the changes from baseline in the apathy/avolition and expressive deficit factors between the BNSS and the PANSS. We hypothesize that the main reason for this decrease in correlation between the two instruments on the factor level is driven by the underlying differences in the construction of the respective scales. Unlike the PANSS, the BNSS addresses all five currently recognized domains of negative symptoms including anhedonia and attempts to differentiate anticipatory from consummatory states. While on the total score level the BNSS and the PANSS negative subscale/negative factor capture change from baseline in a very similar fashion, the differences on the level of the apathy/avolition and expressive deficit factors offer the potential to assess the change from baseline in a more granular way and therefore justify the use of both instruments simultaneously during a clinical trial. We plan to replicate the results on larger datasets.